Community organizing and community building for health and welfare - Minkler, Meredith (Rutgers University Press, 2012)
The third edition of Community Organizing and Community Building for Healthand Welfare provides new and more established ways to approach community building and organizing, from collaborating with communities on assessment and issue selection to using the power of coalition building, media advocacy, and social media to enhance the effectiveness of such work. With a strong emphasis on cultural relevance and humility, this collection offers a wealth of case studies in areas ranging from childhood obesity to immigrant worker rights to health care reform. A "tool kit" of appendixes includes guidelines for assessing coalition effectiveness, exercises for critical reflection on our own power and privilege, and training tools such as "policy bingo." From former organizer and now President Barack Obama to academics and professionals in the fields of public health, social work, urban planning, and community psychology, the book offers a comprehensive vision and on-the-ground examples of the many ways community building and organizing can help us address some of the most intractable health and social problems of our times